After Rio+20: Preparing for Sustainable Retreat? - Nováček, Pavel (Quaestiones Geographicae, 2013)
The industrial age has brought us much good: a higher quality of life which is reflected in better healthcare and education, a longer life expectancy etc. But besides the indisputable benefits, the industrial age has also caused many problems which are now assuming global proportions. In 1987 UN Commission on Environment and Development attempted to propose how to enable people and whole nations to develop while sustaining functioning ecosystems and healthy environment. The key term became “sustainable development”. But problem with sustainable development concept is that it is so vague and “all-embracing”. Its biggest deficiency is the fact that it fails to attempt to even define human needs. The United Nations Conference on Sustainable Development (Rio+20 conference, June 2012) did not change current unsustainable development trends. Therefore we should allow for and ponder the possibility that effort at sustainable development will fail and the human community will experience great civilization turbulence. Maybe it is too late for sustainable development, what we need is a sustainable retreat. Our abilities are limited and promoting sustainable development may prove to be beyond us. In comparison with our ancestors we have much greater opportunities. But this has not been counterbalanced by greater responsibility and foresight. We should explore and study future opportunities and dangers that could occur under certain conditions. These images of possible futures may help to make our present decisions more qualified and responsible.